2015
DOI: 10.2106/jbjs.n.01279
|View full text |Cite
|
Sign up to set email alerts
|

Gait Analysis and Functional Outcome After Calcaneal Fracture

Abstract: This study demonstrated that the subtalar joint range of motion of patients after a calcaneal fracture was related both to the quality of the reduction of the subtalar joint as evaluated on postoperative CT scans and patient-reported functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…The VICON system comprises eight cameras (6 MX3 and 2 T20, running at 200 Hz) for the detection of markers placed on the skin of the lower extremity. The markers were placed on specific anatomic points on the subjects using regular double‐sided tape, according to the guidelines for the OFM . A 10‐m platform was used for patients and healthy subjects to walk on, with the force platform (Kistler 9282E) in the middle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VICON system comprises eight cameras (6 MX3 and 2 T20, running at 200 Hz) for the detection of markers placed on the skin of the lower extremity. The markers were placed on specific anatomic points on the subjects using regular double‐sided tape, according to the guidelines for the OFM . A 10‐m platform was used for patients and healthy subjects to walk on, with the force platform (Kistler 9282E) in the middle.…”
Section: Methodsmentioning
confidence: 99%
“…This was performed by two observers blinded for other results in this study. The kinematic analysis was performed following the OFM protocol described in detail in our previous studies . Patients and healthy subjects were asked to walk in self‐selected normal, slow, and fast speed.…”
Section: Methodsmentioning
confidence: 99%
“…Calcaneal fractures occur with a reported incidence that varies from 11.5 to 13.7 per 100,000 persons per year [1][2][3]. These fractures are known, among orthopaedic healthcare providers, to influence gait and functional outcome negatively [4,5]; moreover, these patients experience a lower quality of life than the general population [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate patients' experiences with their outcome after a calcaneal fracture, patient-reported outcomes should be utilized [9]. Several studies have reported patient-reported outcomes [4,7,8]; however, most studies were performed in trauma level I patients. As a result, there is insufficient information in the current literature that includes trauma level II patients.…”
Section: Introductionmentioning
confidence: 99%
“…One study did calculate correlations between Böhler’s angle and patient-reported outcome measures and ROM during gait. No correlation was found 27. However, it is not clear how they performed their statistical analysis.…”
Section: Discussionmentioning
confidence: 91%